New satellite systems for obtaining data for Geographic information systems - Miroslav Šimčák (Acta Montanistica Slovaca, 2006)
Galileo will be the European global navigation satellite system, providing a highly accurate and a guaranteed global positioning service under the civilian control. It will be inter-operable with GPS and GLONASS, two other global satellite navigation systems. The satellite navigation users in Europe today have take their positions from the US GPS or from the Russian GLONASS satellites. Yet, the military operators of both systems give no guarantee to maintain an uninterrupted service. The main object of this paper is to introduce a new technology of obtaining data for the GIS.